(x-2)(x+8)=-16

Simple and best practice solution for (x-2)(x+8)=-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)(x+8)=-16 equation:



(x-2)(x+8)=-16
We move all terms to the left:
(x-2)(x+8)-(-16)=0
We add all the numbers together, and all the variables
(x-2)(x+8)+16=0
We multiply parentheses ..
(+x^2+8x-2x-16)+16=0
We get rid of parentheses
x^2+8x-2x-16+16=0
We add all the numbers together, and all the variables
x^2+6x=0
a = 1; b = 6; c = 0;
Δ = b2-4ac
Δ = 62-4·1·0
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{36}=6$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-6}{2*1}=\frac{-12}{2} =-6 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+6}{2*1}=\frac{0}{2} =0 $

See similar equations:

| 2(x+2)+6=5(2+x) | | 3x=7+9 | | 11n-2=-2+3n+8n | | r^2+7r-294=0 | | -7x-180=14x+79 | | 36=5u+4u | | (7k+3+5k+7)/2=k+15 | | -76-x=29+2x | | 7+2k=14 | | -5x-3x-2=-8x+2 | | 1=7/12y | | 3(x-1.5)=11.25 | | v/4-15=1 | | 18^2-3x=6 | | 6x-193=-10x+143 | | 5y=2(10)+10 | | 9x-191=49-3x | | -46+10x=44+4x | | 12c+6c=0 | | r3+ 15=19 | | 4.2+1.4x=-1.4 | | 2x+4=14-3 | | 14x-68=11x+34 | | 19=w+22 | | 15x-3=90 | | 3(2x+7)-2(2x-1)=17 | | 8x-20=6+9x | | -4-6x=2(-3+4x)+4(3-x) | | 42=-14b | | 15=w/4-5 | | 2x+20+x+20=180 | | 1/3x+12=3/4x+7 |

Equations solver categories